USING PRAKTIKA AI LEARNING APP TO IMPROVE STUDENTS' MOTIVATION IN ELT AT TOMAKAKA MAMUJU UNIVERSITY - Fatmawati Fatmawati; Muhammad Sahrir Aras (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study is quantitative research. The objective of this study is to examine how significant does the Praktika AI language learning app to improve students’ motivation in ELT at Universitas Tomakaka Mamuju. This study is a pre-experimental with One Group Pretest-Posttest design. This study was conducted at Tomakaka Mamuju University, Jl. Ir H, Juandat, Mamuju Regency. In this research, the result of the pre-test and post-test were compared to determine the significance of the treatment. The sample in this research were the students of English Education department in academic year 2024-2025, totally 18 students. Data was collected by using observation checklist and test. In this study, the results of the pre-test compared to the post- test results after the treatment. The result shows that the t-value is greater than the t-table value, which means that the alternative hypothesis (H1) is accepted and the null hypothesis (HO) is rejected. Therefore, Praktika AI considered effective as a learning tool in enhancing students' motivation in ELT. The use of Praktika AI learning app has been proven effective in helping improve students' motivation in ELT.